Culture of Papaya Explant in Solid - Liquid Media Sequence as a Rapid Method for Producing Multiple Shoots - Chan, Lai Keng; Teo, Chris K. H. (Universiti Putra Malaysia Press, 1994)
Culturing papaya axillary buds obtained from mature field-grown trees on solid MS + 0.1 mg/l BA + 500 mg/ l casein hydrolysate + 0.38 mg/l riboflavin produced less than 2 shoots per explant over a period of2 to 18 weeks. However, 82 times more shoots were produced when the explants were cultured on solid medium for 10 weeks followed by another 10 weeks in liquid medium.